KONSEP KEBUTUHAN DAN KEDUDUKANNYA DALAM ANALISIS KEBIJAKAN SOSIAL - Hobarth Williams Soselisa (Politeknik Kesejahteraan Sosial, 2005)
Suatu Tinjauan Deskriptif Terhadap Kebutuhan Sosial Masyarakat Maluku dan Tantangannya - (Needs Assessment Concept and its Role in Social Policy Analysis: A Descriptive Review on Maluku Community Social Needs and its Challenges).Needs assessment in policy analysis and challenges of Maluku community in the third millennium is determined by the following factors. First, the desired condition of a target population that needs post-conflict improvement. Second, supporting resources to serve as determinants in decision making process for post-conflict program analysis. In making a policy analysis of a target population, its need are determined by the size of geographical area. In target of policy analysis, needs assessment is the determinant of the social needs of Maluku people and how they move away from the current challenges in such a manner that they can finally make their own decisions. Considering the critical role of needs assessment mentioned above, the purpose of this article is to describe empirically the basic needs of the community in a certain condition, to analyze and plan program intervention. In the context of Maluku, the assessment is focused on 1) community basic social needs and 2) challenges for the Mollucans in the Third Millennium.